STUDI PERSAMAAN REGRESI LINEAR UNTUK PENYELESAIAN PERSOALAN DAYA LISTRIK - Ulul Ilmi (Jurnal Teknika, 2019)
Linear regression equation is a mathematical equation in the form of y = a + bx, where x as the variable electric voltage is the independent variable and y as the electric power variable is the dependent variable. Based on the results of the study it can be concluded that the linear regression equation obtained is y = 28.5849 - 0.6569 x. With this equation, every x value increases from zero to one, then the y value decreases by -0.6569. This means that every addition of a voltage value of one volt, the value of electrical power is reduced by - 0.6569 watts. However, every reduction in the value of the electric voltage is minus one volt, then the value of electrical power increases by 0.6569 watts. Based on these results, it can be concluded that the linear regression equation study can be used to solve electrical power problems.